Gene-Environment Interactions and the Risk of Barrett's Esophagus in Three US Cohorts. (June 2019) - Crous-Bou, Marta; Jovani, Manol; De Vivo, Immaculata; Jacobson, Brian C.
Abstract : OBJECTIVES: Several single-nucleotide polymorphisms (SNPs) have been associated with Barrett's esophagus (BE) risk. In addition, environmental factors including smoking, alcohol consumption, and heartburn increase BE risk. However, data on potential interactions between these genetic and environmental factors on BE risk are scant. Understanding how genes and environmental risk factors interact may provide key insight into the pathophysiology of BE, and potentially identify opportunities for targeted prevention and treatment. The objectives of this study were to examine the main effects and the potential effect modification between known genetic loci (SNPs) and established environmental risk factors for BE. METHODS: We performed a nested case-control study using data on 401 incident BE cases and 436 age-matched controls from the Nurses' Health Study, Nurses' Health Study II, and Health Professionals Follow-up Study cohorts, who gave blood and completed biennial questionnaires. Overall, we genotyped 46 SNPs identified in previous BE genome-wide association studies as well as SNPs in candidate genes related to BE susceptibility (i.e., related to excess body fat, fat distribution, factors associated with insulin resistance, and inflammatory mediators). A genetic risk score (GRS) was constructed to evaluate the combined effect of the selected SNPs on BE risk. Interactions between SNPs and BE risk factors were also assessed. RESULTS: We observed a suggestive, but not statistically significant, association between our GRS and BE risk: a one-allele increase in the unweighted GRS increased the risk of BE by a factor of 1.20 (95% confidence interval = 1.00–1.44; P = 0.057). We did not observe any meaningful multiplicative interactions between smoking, alcohol consumption, or heartburn duration and BE genotypes. When we assessed the joint effect of weighted GRS and BE risk factors, we did not observe any significant interaction with alcohol and heartburn duration, whereas smoking showed a significant multiplicative interaction ( P = 0.016). CONCLUSIONS: Our results suggest that SNPs associated with BE at genome-wide significant levels can be combined into a GRS with a potential positive association with BE risk.